Technology Innovations in Colon Targeted Drug Delivery Systems - Meenakshi Jaiswal; S. K. Lanjhiyana (Technology Innovations in Colon Targeted Drug Delivery Systems, 2022)
Drug targeting to colon has numerous advantages into the context of reduction of side effects, lesser chance of dose dumping, lesser drug degradations and successful management of local diseases viz., ulcerative colitis, Crohn’s disease, irritable bowel syndrome, chronic pancreatitis and colon cancer as per reports. These are possible only if those delivery systems are able to target drugs directly into the colon specific region successfully. Drug targeting to colonic region via oral route had been utilized for newer technology-based proteins and peptide types drugs. These colon specific drug delivery systems are more advantageous in many aspects in comparison to available conventional types marketed dosage forms. These colon specific systems are utilizing for obtaining local, topical and/or systemic absorptions for the purpose of possible management of local colon diseases. Colon targeting bypasses those acidic and enzymatic assaults of drugs in upper gastrointestinal tract during oral drug administration. Fewer formulation strategies and mechanisms had been developed by our researchers for obtaining maximum possible benefits of desired pharmacological actions in this regard. This present article is highlighted for colonic drug targeting parameters including novel approaches, physico-chemical features, newer advanced delivery systems, formulation strategies, multiparticulate systems, characterizations of delivery systems, etc.